Effectiveness of Virtual Reality on Postoperative Pain, Disability and Range of Movement after Knee Replacement: A Systematic Review and Meta-Analysis - Jara Esteban-Sopeña; Hector Beltran-Alacreu; Marc Terradas-Monllor; Juan Avendaño-Coy; Nuria García-Magro (Life, 2024)
Postoperative pain after knee arthroplasty (TKA) is a reality that continues to be experienced today. Recently, virtual reality (VR) has demonstrated effectiveness in the management of pain. Our aim was to review the original controlled trials evaluating the effectiveness of VR for pain management and quality of life after TKA. Six databases were searched for articles published from inception to September 2023, following (PRISMA) guidelines. The methodological quality was assessed using the Risk of Bias tool for Randomized Trials (ROB2). Five RCTs were included in the systematic review, and four of them in the meta-analysis. The effectiveness of VR for short term pain relief was superior compared to the control (MD = −0.8 cm; CI 95%: −1.3 to −0.4; p < 0.001). VR showed a greater effect on the secondary outcomes of WOMAC (MD = −4.6 points; CI 95%: −6.5 to −2.6, p < 0.001) and the HSS scale (MD = 6.5 points; CI 95%: 0.04 to 13.0, p = 0.049). However, no differences were found in the effect on the ROM between groups (MD = 3.4 grades; CI 95%: −6.0 to 12.8, p = 0.48). Our findings suggest that the use of virtual reality during the postoperative period could be an effective non-pharmacological therapy in relieving acute pain, compared to a control intervention, with a very low degree of certainty according to the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE). However, the low methodological quality of the articles limits our findings.